Doug Cook : acquiring a business (B) - Rogers, Steve (SAGE Knowledge. Cases., 2017)
Doug Cook, an MBA graduate, was wrestling with one of the most important career decisions of his life: Which one of three seemingly promising businesses should he acquire? Each acquisition was a viable opportunity, and each had potential to be a successful business. Cook, however, had heard numerous disconcerting stories about other entrepreneurs going through this process. He realized that until this time the biggest purchase he had made in his life was a $250,000 condominium in downtown Chicago. Acquiring one of these companies would require a financial and personal commitment greater than anything he had ever attempted. He felt a window of opportunity was closing. If he did not act now, he might find himself in the corporate world forever. Cook began by writing up a personal criteria list for his acquisition, then researching online and media sources for businesses for sale. Frustrated with that process, he hired a business broker. With the brokers help, Cook found three promising candidates from which to choose: Luxury Tassels, Inc.; Feldco Windows and Doors, Inc.; and Coyote Consulting Company. The (A) case includes income statements, pro forma forecasts, balance sheets, and organization charts for each company, in addition to Cooks financial analyses and valuation of each company. The (B) case features the letter of intent that Cook gave the owner of the company he selected. Ultimately he did purchase the company, and in the (C) case, Cook examines pathways to growing his newly acquired company.